Daya Tarik Desa Wisata Edelweis - Fajar Adi Nugroho; Nafis Apta Aginta; M. Habib Nasrullah; Bagaskara Harilinawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Wonokitri Edelweiss Tourism Village is the only tourist village that presents edelweiss flowers as the main attraction, where the edelweiss flower is one of the plants that is protected by law, but the management group has obtained permission to cultivate it, apart from conservation reasons for cultivating edelweiss flowers. This is also closely related to the culture of the Wonokitri village community (Tengger tribe) because this flower is a sacred flower that is used for several traditional ceremonies of the Wonokitri village community.